2017
DOI: 10.3390/buildings7010010
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Monitoring of Occupants’ Thermal Comfort through Infrared Imaging: A Preliminary Study

Abstract: Thermally comfortable indoor environments are of great importance, as modern lifestyles often require people to spend more than 20 h per day indoors. Since most of the thermal comfort models use a variety of different environmental and personal factors that need to be measured or estimated, real-time and continuous assessment of thermal comfort is often not practically feasible. This work presents a cheap and non-invasive approach based on infrared imaging for monitoring the occupants' thermal sensation and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(14 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…Infrared cameras are usually high cost and big size. Oliveira et al, 2007Bouzida et al, 2009Burzo et al, 2014Ranjan and Scott;2016Burzo et al, 2017Pavlin et al, 2017Metzmacher et al, 2018Yoshikawa et al, 2019 Non-invasive measurements (crossvalidation of infrared camera, RGB camera and wearable devices)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infrared cameras are usually high cost and big size. Oliveira et al, 2007Bouzida et al, 2009Burzo et al, 2014Ranjan and Scott;2016Burzo et al, 2017Pavlin et al, 2017Metzmacher et al, 2018Yoshikawa et al, 2019 Non-invasive measurements (crossvalidation of infrared camera, RGB camera and wearable devices)…”
Section: Discussionmentioning
confidence: 99%
“…Infrared camera was widely used for collecting and analyzing infrared images of nude skin such as facial, hand skin (Bouzida et al, 2009;Burzo et al, 2014;Ranjan and Scott;2016;Burzo et al, 2017;Pavlin et al, 2017;Metzmacher et al, 2018), which could be used to control HVAC systems in energy efficient manner without influencing thermal comfort (Ranjan and Scott, 2016). Facial skin temperature was obtained by far-infrared imaging (7-14 μm).…”
Section: Infrared Camera Technologymentioning
confidence: 99%
“…al. utilized a low resolution thermal camera (FLIR Lepton) to extract temperatures from the forehead region and showed that the extracted temperatures were well correlated with thermal sensations [27]. The approach utilized a low-resolution thermal camera however, it was only able to extract crude measurements from the forehead.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Among the non-intrusive techniques, thermal imaging has been more widely studied. Results from previous studies show that thermal imaging can provide useful information towards predicting thermal sensations [10,23,27,29]. However, previous studies have either manually extracted skin temperatures from different regions of interest (ROI) or utilized automated methods that are not very accurate in extracting skin temperatures from different ROIs using a thermal camera.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there are plenty of opportunities to harness recent embedded system technologies in intelligent building automation systems. Particularly, sophisticated computational tasks can be conducted on these embedded systems efficiently, such as real-time video processing and accurate building thermal response simulation (e.g., [13]).…”
Section: Introductionmentioning
confidence: 99%